Philosophy for Children (P4C) in improving critical thinking in a secondary moral education class - Zulkifli, Hafizhah; Hashim, Rosnani (IJLTER, 2020)
The purpose of this study was to identify the effect of Philosophy for Children (P4C) in improving critical thinking among students. The study was conducted via the quasi-experimental research comprising of 27 students placed in the experimental group while the remaining 34 students in the control group. The instrument used was the Ujian Kemahiran Menaakul (Test for Reasoning Skills) Centre for Teaching Thinking (UKMCTT). Based on the statistical t-test on critical thinking, the treatment group scored a higher mean in the post-test mean score compared to the control group, which suggests that P4C had helped to improve students’ critical thinking. The application of P4C allows students to think or reflect on the consequences of the action or assumption they made in their discussion. Simultaneously, it provides career advancement for the teachers by providing the classroom with a new strategy and renewed energy and enthusiasm